ZrMOF nanoparticles as quenchers to conjugate DNA aptamers for target-induced bioimaging and photodynamic therapy. Issue 38 (9th August 2018) - Liu, Yuan; Hou, Weijia; Xia, Lian; Cui, Cheng; Wan, Shuo; Jiang, Ying; Yang, Yu; Wu, Qiong; Qiu, Liping; Tan, Weihong
Abstract : Aptamer conjugated porphyrinic metal–organic framework (MOF) achieved target-induced bioimaging and photodynamic therapy. Abstract : Porphyrinic metal–organic framework (MOF) nanoparticles for photodynamic therapy solve the photosensitizer problems of poor solubility, self-quenching and aggregation. However, their low selectivity towards malignant tissues is an obstacle for bioimaging and a bottle-neck to cellular uptake for highly efficient photodynamic therapy of cancer. Here, ZrMOF nanoparticles as quenchers to conjugate DNA aptamers were developed for target-induced bioimaging and photodynamic therapy. A phosphate-terminal aptamer prepared by solid-phase DNA synthesis was anchored on the surface of ZrMOF nanoparticles through strong coordination between phosphate and zirconium. Based on π–π stacking-induced quenching of TAMRA by ZrMOF nanoparticles, target-induced imaging is achieved due to the structural change of the aptamer upon binding with the target. Aptamer-conjugated ZrMOF nanoparticles with target binding ability significantly enhanced the photodynamic therapy effect. Furthermore, phosphate-terminal aptamer conjugation method can be generalized to other types of MOF nanomaterials, such as UiO-66 and HfMOF nanoparticles, which can be potentially used in biochemistry.